Thermodynamic Assessment of a Solar-Driven Integrated Membrane Reactor for Ethanol Steam Reforming - Hongsheng Wang (MDPI AG, 2021)
To efficiently convert and utilize intermittent solar energy, a novel solar-driven ethanol steam reforming (ESR) system integrated with a membrane reactor is proposed. It has the potential to convert low-grade solar thermal energy into high energy level chemical energy. Driven by chemical potential, hydrogen permeation membranes (HPM) can separate the generated hydrogen and shift the ESR equilibrium forward to increase conversion and thermodynamic efficiency. The thermodynamic and environmental performances are analyzed via numerical simulation under a reaction temperature range of 100–400 °C with permeate pressures of 0.01–0.75 bar. The highest theoretical conversion rate is 98.3% at 100 °C and 0.01 bar, while the highest first-law efficiency, solar-to-fuel efficiency, and exergy efficiency are 82.3%, 45.3%, and 70.4% at 215 °C and 0.20 bar. The standard coal saving rate (SCSR) and carbon dioxide reduction rate (CDRR) are maximums of 101 g·m−2·h−1 and 247 g·m−2·h−1 at 200 °C and 0.20 bar with a hydrogen generation rate of 22.4 mol·m−2·h−1. This study illustrates the feasibility of solar-driven ESR integrated with a membrane reactor and distinguishes a novel approach for distributed hydrogen generation and solar energy utilization and upgradation.